Improvement of the industrial extraction method of methane homologues (Academic journal Industrial Machine Building Civil Engineering, 2023)
Absorption processes are one of the main ones in the preparation of hydrocarbon gases. However, in connection with a decrease in the pressure of the input gas, a number of facilities for the preparation of industrial products cannot provide the necessary technological regime and therefore require reconstruction. A typical example is the installation of low-temperature absorption at the main facilities «Solokha» of the gas industry management «Poltavagasvydobuvannya» where there is a decrease in the efficiency of the separation process of natural and oil gases.  According to the results of analytical studies, to eliminate the indicated shortcoming, a variant of the reconstruction of the ULTA MF «Solokha» is proposed, which involves the use of a scheme with preliminary saturation of the regenerated absorbent. This will increase the extraction rate of components by 21.96%.
Keywords: low-temperature absorption; wide fraction of light hydrocarbons; pre-saturation of the absorbent